2003
DOI: 10.1002/prot.10491
|View full text |Cite
|
Sign up to set email alerts
|

Conformational interconversion in compstatin probed with molecular dynamics simulations

Abstract: Compstatin is a 13-residue cyclic peptide that has the potential to become a therapeutic agent against unregulated complement activation. In our effort to understand the structural and dynamic characteristics of compstatin that form the basis for rational and combinatorial optimization of structure and activity, we performed 1-ns molecular dynamics (MD) simulations. We used as input in the MD simulations the ensemble of 21 lowest energy NMR structures, the average minimized structure, and a global optimization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 46 publications
(84 reference statements)
5
48
0
Order By: Relevance
“…Studies have been reported in which unfavorable entropy changes were ascribed to configurational changes in the ligand upon binding (42) or to protein conformational changes upon binding (43). Molecular dynamic simulations carried out on the ensemble of energy-minimized NMR structures suggested that V4H9 exists as multiple conformers in solution (44). The authors reported five major conformers of compstatin in solution: The most populated is the coil conformation with a type I ␤-turn occupying about 44% of the conformational space, which resembles the average energy minimized conformation obtained from NMR studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have been reported in which unfavorable entropy changes were ascribed to configurational changes in the ligand upon binding (42) or to protein conformational changes upon binding (43). Molecular dynamic simulations carried out on the ensemble of energy-minimized NMR structures suggested that V4H9 exists as multiple conformers in solution (44). The authors reported five major conformers of compstatin in solution: The most populated is the coil conformation with a type I ␤-turn occupying about 44% of the conformational space, which resembles the average energy minimized conformation obtained from NMR studies.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these observations and the negative heat capacity changes observed in the present study, we propose that compstatin exists as a coil before binding and shows a propensity to undergo configurational changes to a more structured ␤-hairpin after binding. This interconversion has a low free energy barrier, showing a higher probability for the peptide to assume a ␤-hairpin conformation from the coil conformation (44).…”
Section: Discussionmentioning
confidence: 99%
“…The original 21 PDB structures are all in coil conformations. However, after minimization, a hhairpin (bcompstatinN 2 ) as well as 3 10 -helix structures (bcompstatinN 18 and bcompstatinN 20 ) [17] appeared (see the third column in Table 2). 3 10 -Helices are formed in the turn position with a relatively high energy.…”
Section: Resultsmentioning
confidence: 99%
“…However, for real proteins, all-atom representations that include all pairwise interactions and solvation effects fail to characterize the energy landscape, since they require astronomical amounts of CPU time. Mallik et al [17] has investigated the energy landscape of compstatin using 1-ns molecular dynamics (MD) simulations starting from the 21 NMR structures [14], using a CHARMM force field with a continuum solvent model. They found three kinds of conformers, coil with a h-turn, h-hairpin with a h-turn, and an a-helix, at the end of their MD simulation.…”
Section: Introductionmentioning
confidence: 99%
“…4). The arsenal of active and inactive analogs in combination with the known solution structures led to the development of sophisticated in silico models based on QSAR, molecular dynamics, or conformational space annealing (Mallik et al 2003;Mulakala et al 2007;Song et al 2005;Tamamis et al 2007). However, the most important breakthrough was reached with the release of the first co-crystal structure between a compstatin analog and C3c (see Chap.…”
mentioning
confidence: 99%